Thermal imprinting modifies adult stress and innate immune responsiveness in the teleost sea bream - Mateus, Ana (2017)
The impact of thermal imprinting on the plasticity of the hypothalamic-pituitary-interrenal (HPI) axis and stress response in an adult ectotherm, the gilthead sea bream (Sparus aurata, L.), during its development was assessed. Fish were reared under 4 thermal regimes, and the resulting adults exposed to acute confinement stress and plasma cortisol levels and genes of the HPI axis were monitored. Changes in immune function, a common result of stress, were also evaluated using histomorphometric measurements of melanomacrophages centers (MMCs) in the head kidney and by monitoring macrophage-related transcripts. Thermal history significantly modified the HPI responsiveness in adult sea bream when eggs and larvae were reared at a higher than optimal temperature (HT, 22 degrees C), and they had a reduced amplitude in their cortisol response and significantly upregulated pituitary pomc and head kidney star transcripts. Additionally, after an acute stress challenge, immune function was modified and the head kidney of adult fish reared during development at high temperatures (HT and LHT, 18-22 degrees C) had a decreased number of MMCs and a significant downregulation of dopachrome tautomerase. Thermal imprinting during development influenced adult sea bream physiology and increased plasma levels of glucose and sodium even in the absence of an acute stress in fish reared under a high-low thermal regime (HLT, 22-18 degrees C). Overall, the results demonstrate that temperature during early development influences the adult HPI axis and immune function in a teleost fish.